The Challenges in Understanding Standards of Educators and Educational Staff - Hamidah, Dian; Rochman, Chaerul; Farida, Ida; Mansyur, Agus Salim (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2022)
This study aims to analyze the achievement of the standards of educators and education staff. It needs to be discussed to ensure the achievement of an institution based on the eight national education standards that have been set. This study uses a qualitative descriptive method with 10 teachers and education staff at different schools and Madrasah in West Java as participants. The instrument used is in the form of a questionnaire with reference to 19 National Education Standard (SNP). This study concluds that (1) the achievement profiles of the standards of teachers and education staff show various results with an average of 81.1% for Islamic Religious Education teachers, and 81.6% for Non-Islamic Religious Education teachers; (2) aspects that have not reached the maximum score are teacher certification, technology and communication competence, and schools or madrasas that have not had Heads of Administrative Personnel who are experienced and certified from designated institutions by the government. The recommendation of this research is the need for a more in-depth and comprehensive study of the competence and eligibility of teachers in schools. This is important because the teachers is the main actors who play a determinant role for success in achieving educational goals.